Neoplasms and novel gammaherpesviruses in critically endangered captive European minks (Mustela lutreola). Issue 2 (20th July 2020) - Nicolas de Francisco, Olga; Esperón, Fernando; Juan‐Sallés, Carles; Ewbank, Ana Carolina; das Neves, Carlos G.; Marco, Alberto; Neves, Elena; Anderson, Neil; Sacristán, Carlos
Abstract: The European mink ( Mustela lutreola ) is a riparian mustelid, considered one of the most endangered carnivores in the world. Alpha, beta and gammaherpesviruses described in mustelids have been occasionally associated with different pathological processes. However, there is no information about the herpesviruses species infecting European minks. In this study, 141 samples of swabs (oral, conjunctival, anal), faeces and tissues from 23 animals were analysed for herpesvirus (HV) using a pan‐HV‐PCR assay. Two different, potentially novel, gammaherpesvirus species were identified in 12 samples from four animals (17.3%), and tentatively named Mustelid gammaherpesvirus‐2 (MUGHV‐2) and MuGHV‐3. Gross examination was performed on dead minks ( n  = 11), while histopathology was performed using available samples from HV‐positive individuals ( n  = 2), identifying several neoplasms, including B‐cell lymphoma (identified by immunohistochemistry) with intralesional syncytia and intranuclear inclusion bodies characteristic of HV ( n  = 1), pulmonary adenocarcinoma ( n  = 1), and biliary ( n  = 1) and preputial ( n  = 1) cystadenomas, as well as other lesions (e.g., axonal vacuolar degeneration [ n  = 2] and neuritis [ n  = 1]). Viral particles, consistent with HVs, were observed by electron microscopy in the mink with neural lymphoma and inclusion bodies. This is the first description of neoplasms and concurrent gammaherpesvirus infection in European minks. The pathological, ultrastructural and PCR findings (MuGHV‐2) in the European mink with lymphoma strongly suggest a potential role for this novel gammaherpesvirus in its pathogenesis, as it has been reported in other HV‐infected species with lymphoma. The occurrence of neural lymphoma with intralesional syncytia and herpesviral inclusions is, however, unique among mammals. Further research is warranted to elucidate the potential oncogenic properties of gammaherpesviruses in European mink and their epidemiology in the wild population.